The determination of driving characteristics of hanoi bus system and their impacts on the emission - Lien, Nguyen Thi Yen; Dung, Nghiem Trung (Vietnam Journal of Science and Technology, 2017)
A GPS with the update rate of 1 Hz was used to collect the real–world driving data of the five bus routes of Hanoi, namely No. 9, 18, 25, 32 and 33, on weekdays and weekends. GPS data were processed and used to simulate the emission by IVE model. The driving characteristics of Hanoi bus system and their impacts on the emission were determined. Results obtained shown that the real –world driving characteristics are different from area to area and affect the emissions of vehicles. This paper, therefore, reconfirms the necessarity of the development of the typical driving cycle before conducting the emission inventory for mobile sources.